Copper(i)-catalyzed radical decarboxylative imidation of carboxylic acids with N-fluoroarylsulfonimides. Issue 74 (23rd August 2016) - Fang, Zhongxue; Feng, Yu; Dong, Hai; Li, Dashan; Tang, Tiandi
Abstract : An efficient copper-catalyzed radical decarboxylative imidation reaction is presented. Abstract : An efficient copper-catalyzed radical decarboxylative imidation reaction is presented. This strategy is carried out through the copper(i )-catalyzed decarboxylative C(sp 3 )–N and C(sp 2 )–N coupling of carboxylic acids with N -fluoroarylsulfonimides. The reaction shows good functional group tolerance and it provides a new approach for decarboxylative imidation. Preliminary mechanistic studies of this transformation suggest an involvement of N-centered radical species.